2019
DOI: 10.1097/rlu.0000000000002879
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Baseline Total Metabolic Tumor Volume Measured on FDG PET in Patients With Richter Syndrome

Abstract: Purpose We evaluated the prognostic value of baseline total metabolic tumor volume (TMTV) measured using pretreatment FDG PET for patients with transformation of chronic lymphocytic leukemia (CLL) into diffuse large B-cell lymphoma (DLBCL). Methods A total of 28 patients with transformation of CLL into DLBCL who had undergone FDG PET before treatment were retrospectively reviewed. Univariate and multivariate analysis of conventional clinicopathologic va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 34 publications
1
29
0
Order By: Relevance
“…The mainstream prognostic imaging biomarkers are baseline metabolic tumor burden (TMTV), baseline total lesion glycolysis (TLG), and SUVmax. All have been associated with overall survival in a wide range of cancers and treatments (38)(39)(40). With the paradigm shift of immunotherapy, authors have evaluated the potential role of appraising host metabolism in lymphoid tissues such as the bone marrow.…”
Section: Metabolic Prognostic Factorsmentioning
confidence: 99%
“…The mainstream prognostic imaging biomarkers are baseline metabolic tumor burden (TMTV), baseline total lesion glycolysis (TLG), and SUVmax. All have been associated with overall survival in a wide range of cancers and treatments (38)(39)(40). With the paradigm shift of immunotherapy, authors have evaluated the potential role of appraising host metabolism in lymphoid tissues such as the bone marrow.…”
Section: Metabolic Prognostic Factorsmentioning
confidence: 99%
“…Baseline volume-based PET parameters, such as total metabolic tumor volume (TMTV) and total lesion glycolysis (TLG), reflecting the tumor burden and metabolism, have been proposed as promising prognostic biomarkers in DLBCL. A growing body of literature shows that baseline TMTV or TLG can be used to risk-stratify patients with DLBCL (10)(11)(12)(13)(14). Furthermore, a recent study reported that TMTV could even allow for identifying a small group of high-risk NCCN-IPI of ≥4 patients with significantly different outcomes (15).…”
Section: Introductionmentioning
confidence: 99%
“…After the revision of the titles and abstracts, 90 records were eliminated because they were not within the field of interest of the research of this review and 44 records were eliminated because they were editorials, comments, case reports, small case series, reviews or conference proceedings. Finally, 13 studies (for a total of 1336 patients affected by CLL who performed 2-[ 18 F]-FDG PET or PET/CT) were screened in their full-text version and included in this systematic review [14][15][16][17][18][19][20][21][22][23][24][25][26] (Figure 1). No additional manuscripts were discovered while checking the references of the selected articles.…”
Section: Literature Searchmentioning
confidence: 99%
“…Tables 1-3 contain the main characteristics and results of the studies included. Of the 13 studies, 10 were of retrospective nature [14][15][16][19][20][21][23][24][25][26] and only 3 were prospective [17,18,22]. In two papers the scanner utilized was PET only [15,24], while in the other 10 cases the scanner used was hybrid PET/CT [14,[16][17][18][20][21][22][23]25,26]; only in one manuscript both techniques were considered [19].…”
Section: Qualitative Analysismentioning
confidence: 99%